The semiotic method: questions and Interrogations - Lorusso, Anna Maria (E|C, 2020)
In this volume it is interesting to note how an opportunity for reflection on the semiotic method has become more the place for a discussion of the discipline than for clarification on the operation of the discipline. Here, for example, there is no longer any trace of the ancient diatribes between "generative" and "interpretative”. From this point of view semiotics seems to have found a balance, opting for a syncretism of schools that I can only appreciate, in the name of greater heuristic efficacy. Instead, there is a restlessness of legitimacy, as if semioticians themselves were beset by the doubt that their methodological tools are not so different from those of more epistemologically defined disciplines (anthropology for example) or are no longer adequate to epoch we live in (made up of big data to read and order, but also of neuroscience to support).